Discovery and Change: Themes of Mental Model Development Among Successful New Farmers - Sandy Bell (Adult Education Research Conference, 2007)
This study explored how a group of farmers developed their mental models of farming. Two themes emerged from the data: (a) Discovery learning plays an important role in model development; (b) When a mental model serves as a barrier to learning an activating event may be necessary for model transformation.